2013
DOI: 10.1162/rest_a_00234
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers from High-Skill Consumption to Low-Skill Labor Markets

Abstract: Census data show that low-skill workers in the United States are increasingly employed in the provision of non-tradeable time-intensive services-such as food preparation and cleaning-that can be broadly thought as substitutes of home production activities. Consumer expenditure data show that the fraction of household spending in these services is increasing with the head's wage rate, consistent with the predictions of standard economic theory. These stylized facts suggest a "consumption story" for how the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(145 citation statements)
references
References 41 publications
12
127
0
6
Order By: Relevance
“…Different explanations have been proposed in the empirical literature to account for polarisation. Beside technology, other factors explaining patterns of job polarisation have included international trade and offshoring [38][39][40][41], consumption spill overs [42,43], ageing of population [44], labour market rigidity [45]. The routinisation hypothesis shifts the analysis from skills to tasks arguing that the introduction of computer capital-on the one hand-substitutes for workers in performing cognitive and manual tasks, on the other hand complements workers in performing non-routine problem-solving tasks.…”
Section: The State Of the Artmentioning
confidence: 99%
“…Different explanations have been proposed in the empirical literature to account for polarisation. Beside technology, other factors explaining patterns of job polarisation have included international trade and offshoring [38][39][40][41], consumption spill overs [42,43], ageing of population [44], labour market rigidity [45]. The routinisation hypothesis shifts the analysis from skills to tasks arguing that the introduction of computer capital-on the one hand-substitutes for workers in performing cognitive and manual tasks, on the other hand complements workers in performing non-routine problem-solving tasks.…”
Section: The State Of the Artmentioning
confidence: 99%
“…In the United States, polarization of jobs has also been linked to growing wage inequality. Based on census data, it was found that the growing share of incomes going to high-skilled workers has increased demand for non-tradeable time-intensive services that are difficult to automate -such as food preparation and cleaning -provided by low-skilled workers (the 'consumption hypothesis') (Mazzolari and Ragusa 2013). Based on data for 16 countries, strong evidence for the routinization hypothesis was found in Europe, and only weak evidence for the effects of offshoring and inequality on job polarization (Goos et al 2009).…”
Section: Determinants Of Job Polarization and Skills Mismatchmentioning
confidence: 99%
“…For a positive impact of rising shares of skilled workers on total employment, low-skilled employment has to have a good employment performance, too. Indeed, a positive indirect impact of high-skilled employment on low-skilled employment is emphasised by Glaeser (2013) and documented for the US during the 1990s by Mazzolari and Ragusa (2013). The related question on whether regional human capital endowments diverge is derived in the economic geography literature as the equilibrium outcome of concentration and dispersion forces.…”
Section: Theoretical Backgroundmentioning
confidence: 99%